The Characteristics, Swelling Ratio and Water Content Percentage of Chitosan-gelatin/limestone-based Carbonate Hydroxyapatite Composite Scaffold - Rianti, Devi; Fanny, Geo; Nathania, Rania Vivian; Purnamasari, Alqomariyah Eka; Putri, Rifayinqa Ruyani; Soekartono, Helal; Soebagio; Yuliati, Anita; Syahrom, Ardiyansyah (International Journal of Integrated Engineering, 2022)
Background: The tissue engineering field has developed a scaffold that can be used to increase the bone regeneration process. Carbonate hydroxyapatite (CHA) is a well-known scaffold due to its components resembling human bones. Methods: The scaffold was synthesized from K, G, and limestone-based CHA using a freeze-drying method with K-G/CHA ratios (w/w) of 40:60, 30:70, 20:80, and 10:90. A Fourier transform infrared spectroscopy (FTIR), a scanning electron microscope-energy dispersive X-ray (SEM-EDX), and X-ray diffraction (XRD) were used to characterize the scaffold. Results: The FTIR test showed some functional groups, such as hydroxyl, amide I, amide II, carbonate, and phosphate. The SEM-EDX test showed micropore (<50 um) and macropores (>50 um) structures as well as elements of C, N, O, Mg, Al, Si, P, and Ca. The XRD analysis obtained crystalline and amorphous particles. The WCP values obtained were 61.29%, 64.30%, 67.71%, and 67.78%. Conclusion: K-G/CHA composite scaffold with a ratio of 30:70 has ideal characteristics, a swelling ratio, and a WCP.